Feasibility of Peritoneal Dialysis in Extremely Low Birth Weight Infants - Francesco Macchini; Agnese De Carli; Sara Testa; Rossella Arnoldi; Stefano Ghirardello; Gianluigi Ardissino; Fabio Mosca; Maurizio Torricelli; Ernesto Leva (EL-Med-Pub, 2012)
Acute renal injury is common in extremely low birth weight (ELBW) infants with a frequency ranging from 8% to 24%. Peritoneal dialysis (PD) has been used only occasionally in ELBW. We report our experience and share the solutions used to tackle the difficulties rising from the small size of this type of patients. PD was successfully performed in three ELBW infants with acute renal failure. A neonatal, single-cuff, straight Tenckhoff catheter was placed in 2 patients, while a Broviac single cuff vascular catheter was used in another. PD was feasible and effective in all children. Leakage was observed with Tenckhoff catheters, but this didn't impair the PD efficacy. The technical difficulties were related to the size and shape of the peritoneal catheters, not easily fitting with the very thin abdominal wall of the preterm infants. We conclude that PD is feasible and effective, can be considered as the rescue therapy in preterm ELBW infants with acute renal failure.